Pengujian Monday Effect pada Indeks LQ-45 di Bursa Efek Indonesia pada saat Pandemi - Kepakisan, Komang Bagus Surya; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi; Vol 31 No 9 (2021), 2021)
Research in Indonesia found many anomalies in the stock market, such as the Phenomenon of Monday effect. The diversity of research results encourages to re-research the Phenomenon of Monday effect on different conditions, namely pandemic. The purpose of this study is to find out the occurrence of Monday effect on the Indonesia Stock Exchange at the time of the pandemic. This research was conducted on all LQ-45 companies in March to October 2020. Data collection by observing the available secondary data. The analysis technique used is one sample t-test. This research proves that there is no difference in average return on Monday which the phenomenon of Monday effect doesn’t occur during a pandemic. Keywords: Monday Effect; LQ-45 Index; Indonesia Stock Exchange.